Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acsami.1c22685
|View full text |Cite
|
Sign up to set email alerts
|

Vaporization-Controlled Energy Release Mechanisms Underlying the Exceptional Reactivity of Magnesium Nanoparticles

Abstract: Magnesium nanoparticles (NPs) offer the potential of high-performance reactive materials from both thermodynamic and kinetic perspectives. However, the fundamental energy release mechanisms and kinetics have not been explored due to the lack of facile synthetic routes to high-purity Mg NPs. Here, a vapor-phase route to surface-pure, core−shell nanoscale Mg particles is presented, whereby controlled evaporation and growth are utilized to tune particle sizes (40−500 nm), and their size-dependent reactivity and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 65 publications
(118 reference statements)
3
29
0
Order By: Relevance
“…The composition of the formulations fabricated have been tabulated in Table S1 in section S4 of the Supporting Information. Constant-volume combustion cell (∼20 cm –3 ) characterization was performed on 25.0 mg of the samples using the setup described in prior works. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the formulations fabricated have been tabulated in Table S1 in section S4 of the Supporting Information. Constant-volume combustion cell (∼20 cm –3 ) characterization was performed on 25.0 mg of the samples using the setup described in prior works. , …”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, exploring binary fuel systems by incorporating energy-dense metal additives, such as Al, Mg, and Ti, in boron powders has been demonstrated as a promising strategy to accelerate B oxidation while maintaining a high energetic content. Employing similar dual fuel systems has been used to control and modulate the transport processes and ignition in thermite mixtures. , Among the metal additives explored thus far, Mg is particularly attractive as a result of its high volatility and reactivity. In our previous work on Mg nanoparticle (NP)-based thermites, we have shown that reducing the particle size of Mg NPs results in their rapid vaporization and a fast vapor-phase Mg release (release time scale of ∼100 μs at a heating rate of 10 5 °C/s) . Additionally, as a result of the highly negative formation energies of MgO compared to B 2 O 3 (Mg lies lower than B in the Ellingham diagram), the reaction between Mg and B 2 O 3 is thermodynamically feasible with a reaction enthalpy (Δ H r ) of ∼ –420 kJ/mol or −2.9 kJ/g.…”
Section: Introductionmentioning
confidence: 99%
“…MgB 2 has been regarded as an interesting candidate for energetic materials as it can store and release a large amount of chemical energy (40 kJ/g), which lies between the gravimetric energy density of Mg (25 kJ/g) and B (58 kJ/g). At the same time, MgB 2 is thermally and chemically more stable than Mg or B; hence, it can help store energy for extended periods. Unlike metal particles, a lower concentration of native oxide is present on the surface of MgB 2 because of the unavailability of Mg or B to form bonds with oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…MgB 2 decomposes into Mg and B at elevated temperatures, which subsequently react with oxygen to form ternary oxides of Mg and B. This avoids the accumulation of B 2 O 3 , which, as a low-temperature melting oxide (450 °C), forms a molten layer that clogs pores and promotes aggregation and sintering during the oxidation of B, thereby delaying the process and reducing its energy output. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation